2015
DOI: 10.1371/journal.pone.0124531
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization Reflects T Cell Composition of Tumor Microenvironment in Pediatric Classical Hodgkin Lymphoma and Has Impact on Survival

Abstract: Macrophages have been implicated in the pathogenesis of classical Hodgkin lymphoma (cHL) and have been suggested to have a negative impact on outcome. Most studies addressing the role of macrophages in cHL have relied on identification of macrophages by generic macrophage antigens, e.g., CD68. We have therefore conducted an in situ analysis of macrophage polarization in a series of 100 pediatric cHL (pcHL) cases using double staining immunohistochemistry, combining CD68 or CD163 with pSTAT1 (M1-like) or CMAF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 73 publications
5
57
0
2
Order By: Relevance
“…124 In a comparative analysis of CD68 and CD163, several studies indicated the superiority of CD163 compared with CD68 for predicting poor prognosis. 120,122,123 Barros et al 125 introduced a new immunohistochemical approach for identifying M1 and M2 macrophages in an analysis of pediatric Hodgkin lymphoma. By using double immunohistochemical staining combining CD68 or CD163 with pSTAT1 (M1-like) or CMAF (M2-like), 100 …”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…124 In a comparative analysis of CD68 and CD163, several studies indicated the superiority of CD163 compared with CD68 for predicting poor prognosis. 120,122,123 Barros et al 125 introduced a new immunohistochemical approach for identifying M1 and M2 macrophages in an analysis of pediatric Hodgkin lymphoma. By using double immunohistochemical staining combining CD68 or CD163 with pSTAT1 (M1-like) or CMAF (M2-like), 100 …”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…For example, the induction of capillary leakiness seen in the brain (175, 176), lung (177), skin (178), etc., which has been associated with upregulation of VEGF (176, 179) and hypoxia (180), is reminiscent of the increased vascular permeability (181, 182), aberrant pro-angiogenic signaling (183, 184) and areas of hypoxia (185, 186) characteristic of many tumors. Similarly, there is a growing understanding of the transition in macrophage state between M1 and M2 associated with the progression of radiation-associated late effects (118); alterations in the M1:M2 ratio are a common feature of the tumor microenvironment (187, 188) and are associated with immune tolerance (189, 190). Furthermore, chronic inflammation is now recognized as major factor in malignant disease (191).…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐CD68 staining was performed to avoid the bias that could be introduced by counting macrophages with H‐RS‐like morphology and with phagocytosed apoptotic debris . CASP3‐positive H‐RS cells were counted using morphologic criteria by computer‐assisted microscopic analysis and were expressed as a percentage of all H‐RS cells. FFPE tonsil specimens were used as a positive control for detection of active CASP3.…”
Section: Methodsmentioning
confidence: 99%